The Cost of Staying Healthy - World Bank (Washington, DC: World Bank, 2020)
Latin America and the Caribbean was hit hard by the Covid-19 pandemic, which arrived on the back of years of disappointing economic growth and limited social progress, and after a wave of social unrest. This report reviews the impacts of the crisis as well as the policy responses by countries, which often involved sizeable social transfers. It also presents growth forecasts, and quarterly growth estimates based on satellite imagery. With countries experiencing a diverse mix of health costs and economic costs, the report analyzes how the effectiveness of containment policies, and their impact on economic activity, differ between richer and poorer countries. It also assesses the cost of staying healthy in normal times, showing how it is affected by the structure of the domestic pharmaceutical sector and by the effectiveness of public procurement of medicines. As the region may have to live with the virus for a while, four policy directions are proposed for discussion.